Local Trends in Price‐to‐Dividend Ratios—Assessment, Predictive Value, and Determinants. Issue 8 (16th December 2016) - HERWARTZ, HELMUT; RENGEL, MALTE; XU, FANG
Abstract : Persistent variations of the log price‐to‐dividend ratio (PD) and their economic determinants have attracted a lively discussion in the literature. We suggest a gradually time‐varying state process to govern the persistence of the PD. The adopted state‐space approach offers favorable model diagnostics and finds particular support in out‐of‐sample stock return prediction. We show that this slowly evolving mean process is jointly shaped by the consumption risk, the demographic structure, and the proportion of firms with traditional dividend payout policy during the past 60 years. In particular, the volatility of consumption growth plays the dominant role.